Comparative efficacy of three pesticides against the tomato red spider mite Tetranychus evansi Baker & Pritchard under laboratory conditions - Bokonon-Ganta, Aimé H. (My University, 2022)
Tetranychus evansi is an important pest of solanaceous crops in Africa, causing important economic damage. Control of T. evansi is mainly achieved chemically. In search for alternative measures, the efciency of Neem Oil in suppressing eggs and adult females of T. evansi was tested in laboratory in comparison to Acarius and Sunpyrifos, two chemical acaricides commonly used in vegetable farms. The mean egg hatching rates varied signifcantly among treatments, ranging from 3.60±0.54% to 60.3±0.16% (P<0.0001). The highest hatching rate was recorded with the Control whereas the lowest ones were recorded with Neem Oil. Mortality of adult female T. evansi also varied signifcantly among treatments, ranging from 48±3% to 100% (P<0.0001). The highest mortality rates were recorded with Neem Oil at D1 whereas the lowest rate was recorded with the Control treatment. Comparison between pesticide showed Neem Oil as the most efcient (100%) followed by Acarius (93%) and Sunpyrifos (78%). Fecundity of pesticide-treated females T. evansi and proportion of eggs that hatched revealed signifcant diferences between Acarius and Sunpyrifos (P<0.0001), while none of the female survived after being in contact with the Neem Oil. Consequently, Neem Oil could seldom induce pesticide resistance in T. evansi populations. It appears from the study that Neem Oil at D1 or D2 was very efective against T. evansi and could therefore be an alternative to synthetic acaricides for an efective control of T. evansi on nightshade or tomato.
Keywords: Solanum macrocarpon · Azadirachta indica · Acaricide · Tetranychidae · Mite pests · Vegetable crops